Efficacy of spirulina in management of oral submucous fibrosis − a systematic review - Kulkarni Rashmi; Kalaskar Ashita; Kalaskar Ritesh; Gupta Neha (EDP Sciences, 2022)
Objective: The aim of this systematic review was to evaluate the efficacy of spirulina in the management of oral submucous fibrosis. Methodology: Databases (MEDLINE via PubMed, Cochrane, EBSCO-host, Scopus, Science Direct, Clinical Trial Registry- India (CTRI) and Google scholar), review articles, bibliographies and related journal were searched from 1st January 2010 to 30th May 2020, using various combinations of MeSH terms and keywords. Results: A total of 5 clinical trials were analysed for the review, of which 4 were randomized controlled trials and 1 was non-randomized controlled trial. Mouth opening and burning sensation were analysed as primary outcome in all 5 studies. For both outcomes some studies reported statistically significant difference whereas others showed non-significant results on comparing with different interventions. Also, high risk of bias was observed among studies after performing quality analysis. Conclusion: Although the studies suggest efficacy of spirulina in management of OSF, but due to the high risk of bias there is a weak evidence regarding the effectiveness of spirulina in treating OSF. So, more uniform and standard trials on larger population should be carried out.